2018
DOI: 10.1111/jvh.12881
|View full text |Cite
|
Sign up to set email alerts
|

Direct medical costs associated with the extrahepatic manifestations of hepatitis C infection in Europe

Abstract: Hepatitis C virus (HCV) infection is a systemic disease associated with both hepatic and extrahepatic manifestations. The burden associated with the hepatic manifestation of HCV infection has been well documented in Europe, although that of HCV extrahepatic manifestations remains unknown. In this study, we estimated the annual direct medical costs associated with HCV extrahepatic manifestations in five European countries. A previously validated economic model was used to estimate the annual direct medical cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Although we did not observe decreased costs in the DAA group among patients without cirrhosis, we believe that over time the savings associated with the avoidance of advanced liver disease and other complications of HCV will be offset, as predicted by several economic investigations in which DAA therapy was found to be cost‐effective in the long term . Furthermore, although we did not study HCV‐associated extrahepatic manifestations in this study, previous investigators found that a large proportion of all‐cause medical costs were attributable to extrahepatic manifestation–related costs in patients with HCV, adding strength to our findings that treatment with DAAs can reduce the high medical costs in patients with HCV by saving in both liver complications and extrahepatic manifestations avoided with cure …”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Although we did not observe decreased costs in the DAA group among patients without cirrhosis, we believe that over time the savings associated with the avoidance of advanced liver disease and other complications of HCV will be offset, as predicted by several economic investigations in which DAA therapy was found to be cost‐effective in the long term . Furthermore, although we did not study HCV‐associated extrahepatic manifestations in this study, previous investigators found that a large proportion of all‐cause medical costs were attributable to extrahepatic manifestation–related costs in patients with HCV, adding strength to our findings that treatment with DAAs can reduce the high medical costs in patients with HCV by saving in both liver complications and extrahepatic manifestations avoided with cure …”
Section: Discussionsupporting
confidence: 47%
“…(16)(17)(18)31) Furthermore, although we did not study HCV-associated extrahepatic manifestations in this study, previous investigators found that a large proportion of all-cause medical costs were attributable to extrahepatic manifestation-related costs in patients with HCV, adding strength to our findings that treatment with DAAs can reduce the high medical costs in patients with HCV by saving in both liver complications and extrahepatic manifestations avoided with cure. (14,32,33) It is important to note that in our economic analysis, we estimated that the costs for at least an 8-week DAA treatment course ranged between approximately $100,467 and $123,086. However, the actual cost paid for the DAA therapy may be significantly less than our estimation considering the high rebates and discounts negotiated between pharmaceutical companies and payers.…”
Section: Discussionmentioning
confidence: 99%
“…After an episode of decompensation, the risk of death in the following year is between 15% and 20% [ 4 ]. Moreover, chronic hepatitis C causes a substantial economic cost on the National Health Services in Europe, mainly due to the management of patients with advanced liver disease stages [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that HCV patients who received anti‐HCV treatment had 30% lower risk of developing CKD . In another study, investigators projected cost savings of €316 million per year owing solely to a decrease in EHMs after treating all HCV patients with direct‐acting antivirals . In the context of similarly high risks of EHMs in HCV‐infected patients from East Asia, it is reasonable to believe that similar savings could be realized; further studies are needed to estimate the economic impact of HCV cure in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are of great concern since HCV infection is associated not only with increased morbidity and mortality but also with economic losses due to decreased worker productivity and impairment of health‐related quality of life . In addition to hepatic manifestations of HCV (cirrhosis, hepatocellular carcinoma, liver‐related mortality), there are extrahepatic manifestations which add to the clinical, economic and quality of life burden of the infection . Well‐known extrahepatic manifestations of HCV infection include mixed cryoglobulinemia, type 2 diabetes mellitus, chronic kidney disease, lymphoma, lichen planus, Sjogren's syndrome, porphyria cutanea tarda, depression, cardiovascular disease, and rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%